Developing the Warehouse Management Online System - Namwong, Sanyanupap; Thongkham, Jaree (Journal of Applied Informatics and Technology, 2022)
This research aims to develop the warehouse management online system for Profarm Limited Partnership. This system can manage stock of product in the warehouse , debtors and creditors. PHP and HTML used to develop the web application and MySQL is used to store the data. Not only Black-box testing are used to evaluate the performance of this system but also 5-level assessment form to assess satisfaction of the population are employed. The experiment results showed that this system can perform well in all functions with a good level of user satisfaction.